Pendidikan Kesehatan Menggunakan Media Leaflet dan Video terhadap Perilaku Preventif Penyakit Demam Berdarah Dengue - Chrisye Natalia Bawimbang; Agust Arthur Laya; Cut Mutiya Bunsal (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
The main health issue faced by Indonesian society today is Dengue Hemorrhagic Fever (DHF).This disease is caused by the bites of Aedes aegypti and Aedes albopictus mosquitoes. The objective of this study is to determine the effect of health education using leaflets and videos on the preventive behavior of dengue fever in Melonguane Village.The research uses a pre-experimental design with the Two Group Pre-test – Post-test Design method.The sample in this study consisted of 32 respondents.Data collection on preventive behavior was conducted using a questionnaire and analyzed using the Wilcoxon statistical test.The research results obtained in the leaflet intervention group showed that before the intervention, the most common behavior was poor, with 7 respondents (43.8%), while after the intervention, the most common behavior was good, with 8 respondents (50.0%).The research results for the video intervention group showed that the most common behavior before the intervention was poor and fair, with 7 respondents (43.8%), whereas after the intervention, the most common behavior was fair, with 10 respondents (50.0%). The Wilcoxon test results for the intervention group with the leaflet showed a p-value of 0.007, which is < α 0.05.Meanwhile, in the video intervention group, a p-value of 0.008 was obtained, which is < α 0.05.Conclusion: There is an influence of health education using leaflet and video media on the preventive behavior of DBD disease in Melonguane Village.Suggestion: Respondents are expected to apply the information obtained from this health education in their daily lives and to disseminate knowledge to family members and the surrounding community